Allelic and epigenetic DNA variation in relation to F1 heterosis manifestation in F1 hybrids of Capsicum annuum L. - M. N. Shapturenko; S. V. Vakula; L. A. Tarutina; T. V. Nikitinskaya; T. V. Pechkovskaya; L. A. Mishin; L. V. Khotyleva (Вавиловский журнал генетики и селекции)
Managing F1 heterosis is one of the major objectives in hybrid crop breeding programs. The classical theory considers the heterozygosity in F1 hybrids to be the main factor contributing to heterosis and therefore presumes a linear relationship between the value of genetic polymorphisms in parental lines and the heterotic response of their F1 offspring. Therefore, the genetic diversity information is viewed as a tool for selection of promising cross-combinations, but results published by different researchers are inconsistent. In this work, we studied the contributions of structural and nonstructural DNA polymorphisms to F1 heterosis manifestation. We used SSR and methyl-sensitive AFLP (MSAP with HpaII and MspI izoshisomers) protocols for obtaining specific patterns for heterotic and nonheterotic F1 hybrids of sweet pepper (Capsicum annuum L.) from a Belarusian breeding program. We found out that a certain portion of heterosis for yield-related traits might be explained by the polymorphism revealed by SSR analysis. According to our data, the total number of polymorphic SSR loci and the ratio of polymorphic and nonpolymorphic loci demonstrate a significant predictive value and can serve as additional prognostic criteria for the selection of promising cross-combinations. From the MSAP assay, we found a relationship between heterosis and the numbers of methylated and nonmethylated DNA loci for yield traits. Our results indicate that cross-hybridization may favor epiallelic modifications in F1 hybrids, presumably responsible for heterosis. Thus, epigenetic DNA variation may explain the absence of a linear relationship between the level of structural DNA divergence and F1 heterosis, as well as the manifestation of heterosis in crosses of related (genetically similar) accessions.